Réponses

2014-01-07T19:48:13+01:00
Bonsoir,

1) Une primitive de (x-1)^5/3 est  \dfrac{(x-1)^{\dfrac{5}{3}+1}}{\dfrac{5}{3}+1}=\dfrac{(x-1)^{\dfrac{5}{3}+\dfrac{3}{3}}}{\dfrac{5}{3}+\dfrac{3}{3}}=\dfrac{(x-1)^{\dfrac{8}{3}}}{\dfrac{8}{3}}=\dfrac{3}{8}(x-1)^{\dfrac{8}{3}}

2) F'(x)=\dfrac{x-1}{x^2-2x-3}\\\\F(x)=\dfrac{1}{2}\times \dfrac{2(x-1)}{x^2-2x-3}\\\\F(x)=\dfrac{1}{2}\times \dfrac{2x-2}{x^2-2x-3}

Donc une primitive de F'(x) est   \dfrac{1}{2}ln|x^2-2x-3|

3)  F'(x)=\dfrac{4x^2}{(x^3+8)^3}\\\\F'(x)=4x^2(x^3+8)^{-3}\\\\F'(x)=\dfrac{4}{3}\times 3x^2(x^3+8)^{-3}

Une primitive de F'(x) est  \dfrac{4}{3}\times\dfrac{(x^3+8)^{-2}}{-2}= \dfrac{-2}{3}\times\dfrac{1}{(x^3+8)^2}= \dfrac{-2}{3(x^3+8)^2}